Structure and functioning of the Lepidoptera community in Ravenelia macowaniana Pazschke fungus galls on Acacia karroo Hayne :prospects for environmental monitoring - Scholtz, Clarke H. (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 1995.